Obtaining Health Care Services for Low-Income Children: A Hierarchy of Needs - DeVoe, Jennifer E. (J Health Care Poor Underserved, 2008)
INTRODUCTION: Basic health care is beyond the reach of many families, partly due to lack of health insurance. Many of those with insurance also experience unmet need and limited access. In this study, low-income parents illuminate barriers to obtaining health care services for their children. METHODS: We surveyed a random sample of families from Oregon’s food stamp population with children eligible for public insurance, based on household income. Mixed-methods included: (1) multivariable analysis of data from 2,681 completed surveys, and (2) qualitative study of written narratives from 722 parents. RESULTS: Lack of health insurance was the most consistent predictor of unmet health care needs in the quantitative analysis. Qualitatively, health insurance instability, lack of access to services despite having insurance, and unaffordable costs were major concerns. CONCLUSIONS: Parents in this low-income population view insurance coverage as different from access to services, and reported a hierarchy of needs. Insurance was the primary concern; access and costs were secondary.